Stipa pennata (Poaceae) on the Kyiv Plateau - Gritsenko V.V. (Ukrainian Botanical Journal, 2020)
The article presents a list of localities of Stipa pennata on the Kyiv Plateau, central Ukraine. A schematic map of the species distribution and sources of information are provided. During 1907–2018, S. pennata was recorded in the area in 22 localities. The species occurs in both primary and secondary habitats. Regressive changes in the overall distribution (dynamic chorology) of S. pennata on the Kyiv Plateau associated with anthropogenic factors have been revealed. To date, S. pennata has not survived in nine localities. The species disappeared in the areas within the city of Kyiv, in Bila Tserkva and Kaniv towns, as well as in Kaniv Nature Reserve. There are apparently four currently extinct localities of S. pennata reported more than 85 years ago and one locality destroyed as a result of human activities. In June 2018, a new locality of S. pennata was discovered in the southern part of the town of Rzhyshchiv, Kyiv Region, in the Berezovka tract. The vegetation cover of this site is characterized. The species is confined to the top and slopes of a high hill. The population of S. pennata is located in the area of several hectares and is characterized by a large number of individuals of different age groups, predominantly with mature generative individuals. Anemochoric dissemination was observed. The structural features of fruits related to this mode of dissemination / dispersal, viz. the basis and awn of the caryopsis ("grain"), are characterized and illustrated. In order to protect S. pennata within the Berezovka tract in situ, it is proposed to establish a botanical reserve of local importance.